Effect of epidural levobupivacaine with or without dexamethasone soaked in gelfoam for postoperative analgesia after lumbar laminectomy: A double blind, randomised, controlled trial - Kamlesh Kumari; Manoj Kamal; Geeta Singariya; Rama Kishan; Sunil Garg; Sharad Thanvi (Indian Journal of Anaesthesia, 2018)
Background and Aims: Postoperative pain results in prolonged hospital stay and delayed return to normal activity. This study was conducted with the aim of evaluating the analgesic efficacy of gelfoam soaked in levobupivacaine with or without dexamethasone placed in the epidural space in patients undergoing lumbar laminectomy. Methods: Ninety adult patients were randomised into three groups. Gelfoam was soaked in 12 mL of 0.9% sodium chloride in Group P, 10 mL of 0.25% levobupivacaine + 2 mL of 0.9% sodium chloride in Group L, and 10 mL of 0.25% levobupivacaine + 2 mL of dexamethasone in group LD. The primary outcome was time to first request for rescue analgesia. Total 24-h tramadol consumption, and postoperative visual analog scale (VAS) scores were recorded. Chi-square test and analysis of variance test were used, and P < 0.05 was considered significant. Results: 75 patients completed the study. Time to first rescue analgesia was longer in group LD [10.11 ± 3.10 h] compared with group L [6.48 ± 2.36 h] and group P [1.76 ± 1.13 h]. Total 24-h tramadol consumption was lower in group LD (88 ± 66.58 mg) and group L (120 ± 70.7 mg) compared with group P (280 ± 64.5 mg). Postoperative VAS scores were lower in group LD and group L compared with group P, both at rest and on movement. Conclusion: Epidural gelfoam soaked in levobupivacaine and dexamethasone prolongs the duration of analgesia and decreases rescue analgesic consumption and VAS score postoperatively, in patients undergoing lumbar laminectomy.